THE ROLE OF NATIONAL DEBTS IN THE DETERMINATION OF THE YEN‐DOLLAR EXCHANGE RATE. - Litsios, Ioannis; Pilbeam, Keith (Economic Inquiry, 2019)
An intertemporal optimization model is developed to examine the determinants of the long‐run nominal yen‐dollar exchange rate in the presence of national debts. The model is tested empirically using data from Japan and the United States. The proposed theoretical specification is well supported by the data and shows that relative national debts as well as monetary and financial factors may play a significant role in the determination of the long‐run nominal exchange rate between the yen and the dollar.